The relationships between dung beetles and monkeys in the Neotropical region - Halffter, Gonzalo; Favila, Mario E. (Frontiers in Ecology and Evolution, 2023)
The relationship between dung beetles and arboreal mammals has been scarcely studied, and many of the reports refer to observations without a standardized methodology. The accelerated loss of tropical forests urges us to understand this mutualistic association. Using our studies on arboreal dung beetles in the Palenque Archaeological Zone-National Park, Mexico, as a baseline, we analyzed the information on arboreal dung beetles in Neotropical forests in Mexico and around the world. Canthon euryscelis Bates, 1867, Canthon angustatus Harold, 1867, Canthon subhyalinus Harold, 1867, and Canthon femoralis (Chevrolat, 1834) are the main species collected in trees of Palenque, Onthophagus maya Zunino, 1981 and other non-Scarabaeinae species were occasionally collected from trees in Palenque. The small Canthon species are skilled fliers strongly relationship with monkeys in Palenque and other tropical regions of Mexico and Central America. In South America, arboreal dung beetles are more diverse and include these and other dung beetle species associated with monkeys. Several dung beetle species of the genus Onthophagus have been reported in association with African monkeys. In India, several studies report a wide variety of dung beetle species associated with monkeys. In Australia and New Guinea, only some species of Macropocopris are described as being associated with arboreal monkeys, but in Borneo, several dung beetle species have been observed associated with arboreal monkeys, mostly in managed forests. In Madagascar, Arachnoides gandi is the only beetle species reported in trees. We need to formulate a systematic and comparative methodology to understand better how arboreal beetles search for food, where the food is located, how brood balls are made, how male-female pairs meet and nest, and how they contribute to arboreal dung recycling.